LINGUISTIC ASPECT OF EDUCATIONAL PHRASEOGRAPHY (Academia Science Repository, 2023)
This article discusses the national phraseological image of the world in phraseological dictionaries, the issues of creating educational-didactic, communicative and anthropocentric modern educational phraseological dictionaries for schoolchildren, as well as the concept of developing educational phraseography.